Development Of Penta-Axial Geophone For P- And S-Wave In Seismic Downhole Method - Yusoh, Rais (2020)
Seismic downhole is a geophysical method that measures the soil/rock velocity of geological subsurface boundaries in the proximity around borehole. Velocity of seismic wave captured by geophone inside the borehole is transmitted from a source located on the ground surface adjacent to borehole in the form of compressional and shear wave (P- and S-wave). These measurements can be further calculated for site development, liquefaction potential studies and earthwork foundation designs. However, seismic downhole needs an accurate measurement to correlate with geotechnical design parameters such as poisson’s ratio as well as shear and Young’s modulus. The accuracy of seismic downhole depends on the effectiveness of seismic source and the signal to noise ratio. To acquire the maximum amplitude of seismic wave signal, it is important to understand the directional movement of seismic wave source where it should be aligned with geophone sensors. Hence, research on multiple direction of geophone has been performed to retrieve various directions of seismic wave source. Therefore, the aim of this research is to develop the Penta-Axial geophone, consists of five angles geophone (single P-wave and four S-wave geophone) to optimize the effectiveness of receiver. By producing the Penta-Axial geophone, positioning of seismic wave source on surface become effortless, since the receiver is able to acquire various wave direction inside the borehole. Fabrications of Penta-Axial geophones were made using a 3D printer produced by Polyactic Acid (PLA) plastic material as a chassis to hold the geophone sensors position. In addition, a proper data processing spreadsheet was developed to manage the data by sorting the position of traces for each geophone at every depth.